2009
DOI: 10.1007/s12034-009-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, thermal and biological studies of coordination compounds of sulfasalazine drug: Mn(II), Hg(II), Cr(III), ZrO(II), VO(II) and Y(III) transition metal complexes

Abstract: The complexations of sulfasalazine (H 3 Suz) with some of transition metals have been investigated. Three types of complexes, [Mn(HSuz) -2 (H 2 O) 4 ]⋅2H 2 O, [M(HSuz) -2 (H 2 O) 2 ]⋅xH 2 O (M = Hg(II), ZrO(II) and VO(II), x = 4, 8 and 6, respectively) and [M(HSuz) -2 (Cl)(H 2 O) 3 ]⋅xH 2 O (M = Cr (III) and Y(III), x = 5 and 6, respectively) were obtained and characterized by physicochemical and spectroscopic methods. The IR spectra of the complexes suggest that the sulfasalazine behaves as a monoanionic bide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The UV-Vis spectra of sulfasalazine and their complexes in DMSO exhibit and detect peaks [22]. There are two absorption maxima peaks at ranges from 215-340 nm and 350-500 nm, assigned to π-π* and n-π* transitions within the organic moiety of sulfasalazine ligand.…”
Section: Sulfasalazine Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The UV-Vis spectra of sulfasalazine and their complexes in DMSO exhibit and detect peaks [22]. There are two absorption maxima peaks at ranges from 215-340 nm and 350-500 nm, assigned to π-π* and n-π* transitions within the organic moiety of sulfasalazine ligand.…”
Section: Sulfasalazine Complexesmentioning
confidence: 99%
“…The infrared spectra of sulfasalazine [22] and its com-plexes exhibited with the main coordination bands which reveal the mode of bonding. Concerning the sulfasalazine com-plex, the most important region in the infrared spectra of allcomplexes and the H 3 Suz free ligand (~1700-1300 cm ).…”
Section: Coordination Mode Of Sulfasalazine Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…To a solution of 5,5dimethylcyclohexane-1,3-dione (A) ( 1g,7.142 mmole) in ethanol (10ml), (5) drops of glacial acetic acid were added slowly, then the mixture was added to 4 -amino antipyrine (B) (2.905 g, 14.280 mmole) in ethanol (10 ml). The mixture was refluxed for (4hrs), with stirring at temperature (40 -50 ºc) in water path.…”
Section: Preparation Of the Ligandmentioning
confidence: 99%
“…Subsequent studies revealed more rapid clinical response and faster action when combining sulfadoxine with pyrimethamine against falciparum and vivax malaria, including chloroquine resistant strains, in Southeast Asia and Africa [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. In the literature survey, the synthesis and characterization of sulfa drugs complexes with some metal ions have been described [39][40][41][42][43][44][45][46][47][48]. In this article, the coordination mode of sulfadoxine chelating via metal ions such as Ca(II), Mg(II), Zn(II), Fe(III), and VO(II) have been investigated.…”
Section: Introductionmentioning
confidence: 99%